The Effect Of Meridian Acupoint Massage On Fatigue, And Prevention Of Post Partum Depression During The Public Period - Anuhgera, Diah Evawanna; Nikmah Jalila Ritonga (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
Postpartum fatigue is a feeling of tiredness experienced by around 65-80% of mothers after giving birth. Fatigue can trigger post partum depression during the postpartum period. In Indonesia, the incidence of post partum blues is 50% -70%. One of the method is meridian accupoints massage intervention to reduce fatigue and prevent post partum depression. This study aims to analyze the effects of meridian accupoint massage on fatigue and prevention post partum depression in the post partum period. A quasi experimental design with pretest posttest nonequivalent control group was utilized. The study group consisted of 28 postpartum women on the 5th day at the Nining Lubuk Pakam Clinic. The instrument used to measure fatigue is th. e Postpartum Fatique Scale, prevention of post partum depression is measured by the Edinburgh Postnatal Depression Scale (EPDS). Data analysis uses independent and dependent t-tests. The experimental group demonstrated a significantly larger decrease compared with the control groupin measures of fatique and prevention post partum depressive. There was a significant difference in maternal fatigue and prevention of post partum depression after meridian accupoint massage between the intervention group and the control group with a value of p=0.003; p=0.002. The average reduction in fatigue after meridian accupoint massage was 27.11%, while the reduction in stress as an assessment for preventing post partum depression was 43.41%. Meridian Accupoint Massage has been proven to have an influence on reducing fatigue and preventing post partum depression during the postpartum period. For midwives to be able to learn and apply this method to normal postpartum mothers in order to improve the quality of life of postpartum mothers. Meridian accupoint massage intervention can be used as learning material in complementary therapy during the postpartum period.